Reading matters An Unfestschrift for Regina Bendix - Marzolph, Ulrich (Universitätsverlag Göttingen, 2023)
The present book is a special gift for a special colleague and friend. Defined as an "Unfestschrift," it gives colleagues, students, and friends of Regina Bendix an opportunity to express their esteem for Regina's inspiration, cooperation, leader¬ship, and friendship in an adequate and lasting manner. The title of the present book, Reading Matters, is as close as possible to an English equivalent of the beautiful German double entendre Erlesenes (meaning both "something read/a reading" and "something exquisite"). Presenting "matters for reading," the Unfestschrift unites short contributions about "readings" that "mattered" in some way or another for the contributors, readings that had an impact on their understanding of whatever they were at some time or presently are interested in. The term "readings" is understood widely. Since most of the invited contributors are academics, the term implies, in the first place, readings of an academic or scholarly nature. In a wider notion, however, "readings" also refer to any other piece of literature, the perception of a piece of art (a painting, a sculpture, a performance), listening to music, appreciating a "folkloric" performance or a fieldwork experience, or just anything else whose "reading" or individual perception has been meaningful for the contributors in different ways. Contrary to a strictly scholarly treatment of a given topic in which the author often disappears behind the subject, the presentations unveil and highlight the contributor's personal involve¬ment, and thus a dimension of crucial importance for ethnographers such as the dedicatee.